Threshold Change in CEA as a Predictor of Non-Progression to First-Line Systemic Therapy in Metastatic Colorectal Cancer Patients With Elevated CEA. (17th February 2020) - Gulhati, Pat; Yin, Jun; Pederson, Levi; Schmoll, Hans-Joachim; Hoff, Paulo; Douillard, Jean-Yves; Hecht, J Randolph; Tournigand, Christophe; Tebbut, Niall; Chibaudel, Benoist; Gramont, Aimery De; Shi, Qian; et al.
Abstract: Background: Carcinoembryonic antigen (CEA) levels are used in conjunction with imaging to monitor response to systemic therapy in metastatic colorectal cancer (mCRC). We sought to identify a threshold for CEA change from baseline to predict progressive disease (PD) in mCRC patients receiving first-line therapy. Methods: Patients from trials collected in the ARCAD database were included if baseline CEA was at least 10 ng/mL and repeat CEA was available within 14 days of first restaging scan. Optimal cutoffs for CEA change were identified by receiver operating characteristic analysis. Prediction performance of cutoffs was evaluated by sensitivity, specificity, and negative predictive value. Analyses were conducted by treatment class: chemotherapy alone, chemotherapy with anti-VEGF antibody, and chemotherapy with anti-EGFR antibody. Results: A total of 2643 mCRC patients treated with systemic therapy were included. Median percent change of CEA from baseline to first restaging for patients with complete response, partial response, or stable disease (non-PD) and PD was −53.1% and +23.6% for chemotherapy alone (n   =   957) and −71.7% and −45.3% for chemotherapy with anti-VEGF antibody (n   =   1355). The optimal area under the curve cutoff for differentiating PD from non-PD on first restaging was −7.5% for chemotherapy alone and −62.0% for chemotherapy with anti-VEGF antibody; chemotherapy alone, adjusted odds ratio = 6.51 (95% CI = 3.31 to 12.83, P  < .001), chemotherapy with anti-VEGF antibody, adjusted odds ratio = 3.45 (95% CI = 1.93 to 6.18, P  < .001). A 99% negative predictive value clinical cutoff for prediction of non-PD would avoid CT scan at first restaging in 21.0% of chemotherapy alone and 16.2% of chemotherapy with anti-VEGF antibody–treated patients. Among patients with stable disease on first restaging, those with decreased CEA from baseline had statistically significantly improved progression-free and overall survival. Conclusions: Change in CEA from baseline to first restaging can accurately predict non-progression and correlates with long-term outcomes in patients receiving systemic chemotherapy.